A Discourse Analysis of Posters on Saving Environment in English and Vietnamese - Nguyễn Thuận Tuyết Sương (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The aim of this thesis is to carry out a discourse analysis of posters on saving environment in English and Vietnamese to find out their discourse features such as layout, lexical choice, cohesive and stylistic devices. Besides, this study will discover similarities and differences of these features between the two languages. In addition, the research is expected to help poster designers in setting their purposes as well as to find out the ways that posters can make readers understand the messages they convey